The Influence of Knowledge, Lifestyle and Culture on the Incidence of Tuberculosis A Literature Review - Aloto Ximenes Belo Amaral; Mateus Sakundarno Adi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: TB is a public health problem whose incidence is still high in Timor Leste. TB is an infectiousdisease which is one of the leading causes of death in the world caused by an infectious agent Mycobacteriumtuberculosis. The purpose of this study was to review scientific articles focusing on the Influence ofKnowledge, Lifestyle and Culture on the Incidence of Tuberculosis. Method: The method used was aliterature review. Articles used as literature review materials came from SagePub, BMC Public Health,Elsevier, Google Scholar, Pubmed, Proquest and others. The articles were selected based on the researchfocus, which was the Influence of Knowledge, Lifestyle and Culture on the Incidence of Tuberculosis.Results and Conclusions: Knowledge is very important in TB control efforts. Good knowledge needs to befollowed by a good perception. Such knowledge is not only for the TB patients but also for the families andhealth workers. Lifestyles that are very risky to increase health vulnerability in TB patients are smoking,drinking alcohol, using illegal drugs, inadequate consumption, living in a slum environment, lack of airventilation, lack of exercise, lack of sleep, urban life, lack of glycemic control, sugar consumption, andliving with TB patients. Cultural influences include inter-racial disparities, culture of seeking local treatmentor not going to health facilities, delay in initial screening, TB sputum examination, lack of PPE, poor localTB surveillance, traditional medicine, stigma and culture carried by